Generación de Nubes de Puntos 3D con Escáner Laser Terrestre. Georreferenciación y Evaluación de la Calidad - Falip, Sofia; Del Cogliano, Daniel (Ingeniería, 2019)
Context: LIDAR technique allows the 3D modeling of structures with an unprecedented resolution and millimetric precision. This technology is naturally related to Surveying, even more when models are linked to geodesic and vertical reference systems. Diverse LIDAR surveys should be geometrically linked with topographic classic techniques or with geodetic methods such as GNSS. Such linkage conditions the geometric external quality of the integrated model. In order to compare 3D models of millimetric quality through time, the accuracy of the geodetic determinations should be validated. Method: Two buildings that belong to the National University of La Plata were surveyed with TLS (terrestrial laser scanning). These scanners measure the visible surface. Therefore, the complete survey of any complex object requires a series of stations of registration. The final product results from the spatial vinculation of the different adjacent point clouds. In order to do that, there are different techniques. The one used in this case is that of common elements identified from neighboring stations. The results referred to a terrestrial geodetic frame were obtained through a polygonal based on measurements of total stations, automatic level and GNSS. The quality of the 3D final models obtained was assessed internally considering the processing statistical parameters, and externally through the coordinates of control points obtained with independent methods. Results: The internal geometric quality of the point clouds generated with the TLS Trimble TX5, was estimated in 1 to 3 millimeters (1RMS). The classical topographic techniques used in the polygonal gave a coherence of 3 mm in each components, while for the georeferencing obtained with GNSS measurements was 1 cm. Conclusions: The internal geometric quality of the 3D models shows the capacity of representation of LIDAR and its potential for internal deformations’ analysis. The different 3D point clouds, initially dissociated, can be integrated through geodetic-topographic methods, and expressed in a suitable geodetic reference frame.